2000
DOI: 10.1530/eje.0.1420393
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of UT-OC-3 ovarian carcinoma cells by cytokines: inhibitory effects on cell proliferation and activation of transcription factors AP-1 and NF-kappaB

Abstract: The present study was designed to investigate the growth regulatory effects of cytokines in UT-OC-3 ovarian cystadenocarcinoma cells in vitro. The effects of interleukin-6 (IL-6), interferons a (IFN-a) and g (IFN-g), granulocyte-macrophage colony-stimulating factor (GM-CSF), tumour necrosis factor a (TNF-a), and transforming growth factor b1 (TGF-b1) were investigated by 125 I-deoxyuridine ( 125 IUdR) incorporation assay. In order to understand better the molecular mechanisms of the observed effects, the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Here, we report on the antineoplastic effects of IFNγ, a cytokine which has already been shown to exert growth inhibitory effects in vitro in several non-neuroendocrine cancer models, including breast [27], hepatocellular [28], ovarian [29] and colorectal carcinoma [30,31] or glioblastoma [32]. Also in vivo , IFNγ has been demonstrated to be beneficial as a first line therapeutic agent for ovarian cancer [33] or as a supportive drug for enhanced chemoimmunotherapeutic regimes of metastatic melanoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report on the antineoplastic effects of IFNγ, a cytokine which has already been shown to exert growth inhibitory effects in vitro in several non-neuroendocrine cancer models, including breast [27], hepatocellular [28], ovarian [29] and colorectal carcinoma [30,31] or glioblastoma [32]. Also in vivo , IFNγ has been demonstrated to be beneficial as a first line therapeutic agent for ovarian cancer [33] or as a supportive drug for enhanced chemoimmunotherapeutic regimes of metastatic melanoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in rats, c-jun mRNA depression and endometrial epithelial cell proliferation were suggested to be linked (104). In UT-OC-3 ovarian cancer cells, cytokines have inhibitory effects on cell proliferation and activate AP-1 and NFkB (105). As the antiproliferative GnRH agonist triptorelin activates the JNK/c-jun pathway and JNK/c-jun was found to be involved in downregulation of cell proliferation in different systems, it seems reasonable to speculate that the JNK/c-jun pathway is involved in the antiproliferative actions of the GnRH agonist triptorelin.…”
Section: Additional Signaling Mechanismsmentioning
confidence: 99%
“…In a study on rats, c-jun mRNA depression and endometrial epithelial cell proliferation were suggested to be linked (49). In UT-OC-3 ovarian cancer cells cytokines have inhibitory effects on cell proliferation and activate AP-1 and NFkB (50). Because triptorelin activates the JNK/c-jun pathway and JNK/c-jun was found to be involved in down-regulation of cell proliferation in different systems, it seems reasonable to speculate that the JNK/c-jun pathway is involved in the antiproliferative actions of this agonist.…”
Section: Discussionmentioning
confidence: 99%